A Study of Patient Experience Using a Blood Glucose Meter With an In-Built Insulin Dose Calculator. (July 2014) - Ramtoola, Shenaz; Jude, Edward; Robinson, Anthony; Malik, Iqbal; Rayman, Gerrard; Dang, Cuong; Martin, Graham David Ross; Ali, Amar
Accurate calculation and adjustment of insulin doses is integral to maintaining glycemic control in insulin treated patients. Difficulties with insulin dose calculations may lead to poor adherence to blood glucose monitoring and insulin treatment regimes, resulting in poor metabolic control. The main objective of this study was to evaluate ease of use and user preference of a high specification touch screen blood glucose meter, which has an in-built insulin calculator, compared to patients' usual method of testing blood glucose and deciding insulin doses. Patients with diabetes on a multiple daily injection insulin regime used the Test Meter without the insulin calculator and 1 of 3 comparator meters, each for a 7-day period. They then used the Test Meter with the in-built calculator for 10 days. Patients completed an ease of use questionnaire after each 7-day period, a preference questionnaire after the second 7-day period, and a questionnaire comparing the Test Meter with their usual method after the final 10-day period. Of 164 patients who completed the study, 76% stated a preference for the Test Meter as a diabetes management tool compared to their usual method. A small number of patients preferred familiar methods and/or calculating insulin doses themselves. The log book function of meters was important to most patients. The Test Meter system with in-built insulin calculator supports people to better manage their diabetes and increases their confidence. Patients have different needs and preferences which should be acknowledged and supported in a patient centered health service.